2020
DOI: 10.21203/rs.3.rs-16103/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Availability and affordability of essential medicines and diagnostic tests for diabetes mellitus in sub-Saharan Africa: A systematic review.

Abstract: Background Currently, sub-Saharan Africa (SSA) is experiencing a steady increase in the prevalence of diabetes mellitus (DM) coupled with a prevailing high burden of communicable diseases. To effectively address this burgeoning burden of DM, optimal access to affordable essential medicines and diagnostic tests for DM in healthcare systems should be prioritised. We conducted a systematic review of the evidence on the availability and affordability of essential medicines and diagnostic tests for DM in SSA as rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(60 reference statements)
0
3
0
Order By: Relevance
“… 22 The results of the current review consistent with other studies conducted in LMIC demonstrated sub-optimal availability of basic technologies (diagnostic tests, basic equipment) for NCDs, there are many LMIC does not able to provide basic NCDs interventions. 5 , 23 , 24 A possible explanation of sub-optimal availability of basic technologies is in the present period of global fiscal restraint, governments are seeking ways of decreasing expenditures on social sectors, including health. 24 Enhancing the access to essential medicines and basic technologies is important for the accomplishment of the Millennium Development Goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 The results of the current review consistent with other studies conducted in LMIC demonstrated sub-optimal availability of basic technologies (diagnostic tests, basic equipment) for NCDs, there are many LMIC does not able to provide basic NCDs interventions. 5 , 23 , 24 A possible explanation of sub-optimal availability of basic technologies is in the present period of global fiscal restraint, governments are seeking ways of decreasing expenditures on social sectors, including health. 24 Enhancing the access to essential medicines and basic technologies is important for the accomplishment of the Millennium Development Goals.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Inadequate financial resources, one of the major reason for gaps identified, the next stage that could be taken as the remedial stage encourages the efficiency of NCDs services delivery, which can be done throughput priorities for NCDs interventions based on equity, safety, and cost-effectiveness, healthcare providers must be adherence to prescription and investigations requests based on evidence-based and cost-effectiveness. 5 , 23 , 28 If these prioritized interventions are delivered validly, it will enhance the chances of prevention and control of NCDs, and reducing health care budgets. 29 - 31 The study demonstrated that the international community should assist the low-middle-income countries to NCDs control, including increasing access to essential medicines and basic technologies, and support local production of essential medicines.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that nearly half (46%) of all deaths in the region will be attributable to NCDs by 2030, representing a two-fold increase from 25% in 2004 [4]. However, national health systems in SSA appear largely ill-prepared to meet this challenge [5][6][7][8]. Continuity of care across the lifespan and care settings is one of the critical elements of chronic diseases programs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%